Biological and genomic characteristics of two bacteriophages isolated from sewage, using one multidrug-resistant and one non-multidrug-resistant strain of Klebsiella pneumoniae - Liang, Bingchun; Zhao, Wenpeng; Han, Bo; Barkema, Herman W.; Niu, Yan D.; Liu, Yongxia; Kastelic, John P.; Gao, Jian (Frontiers in Microbiology, 2022)
Bovine mastitis caused by multi-drug resistant (MDR) Klebsiella pneumoniae is difficult to treat with antibiotics, whereas bacteriophages may be a viable alternative. Our objective was to use 2 K. pneumoniae strains, 1 MDR and the other non-MDR, to isolate phages from sewage samples and compare their biological and genomic characteristics. Additionally, phage infected mouse mammary gland was also analyzed by H&E staining and ELISA kits to compare morphology and inflammatory factors, respectively. Based on assessments with double agar plates and transmission electron microscopy, phage CM_Kpn_HB132952 had clear plaques surrounded by translucent halos on the bacterial lawn of K. pneumoniae KPHB132952 and belonged to Siphoviridae, whereas phage CM_Kpn_HB143742 formed a clear plaque on the bacterial lawn of K. pneumoniae KPHB143742 and belonged to Podoviridae. In 1-step growth curves, CM_Kpn_HB132952 and CM_Kpn_HB143742 had burst sizes of 0.34 and 0.73 log10 PFU/mL, respectively. The former had a latent period of 50 min and an optimal multiplicity of infection (MOI) of 0.01, whereas for the latter, the latent period was 30 min (MOI=1). Phage CM_Kpn_HB132952 had better thermal and acid-base stability than phage CM_Kpn_HB143742. Additionally, both phages had the same host range rate but different host ranges. Based on Illumina NovaSeq, phages CM_Kpn_HB132952 and CM_Kpn_HB143742 had 140 and 145 predicted genes, respectively. Genomic sequencing and phylogenetic tree analysis indicated that both phages were novel phages belonging to the Klebsiella family. Additionally, the histopathological structure and inflammatory factors TNF-α and IL-1β were not significantly different among phage groups and the control group. In conclusion, using 1 MDR and 1 non-MDR strain of K. pneumoniae, we successfully isolated 2 phages from the same sewage sample, and demonstrated that they had distinct biological and genomic characteristics.